2011
DOI: 10.1681/asn.2010121321
|View full text |Cite
|
Sign up to set email alerts
|

GFR Normalized to Total Body Water Allows Comparisons across Genders and Body Sizes

Abstract: The normalization of GFR to a standardized body-surface area of 1.73 m 2 impedes comparison of GFR across individuals of different genders, heights, or weights. Ideally, GFR should be normalized to a parameter that best explains variation in GFR. Here, we measured true GFR by iohexol clearance in a representative sample of 1627 individuals from the general population who did not have diabetes, cardiovascular disease, or kidney disease. We also estimated total body water (TBW), extracellular fluid volume, lean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Indeed, if non-indexed GFR is considered, there is an expected difference of mGFR in men and women as body size is different according to gender. This point has been nicely illustrated in the RENIS cohort study [31] . Also, we and others have criticized the indexation of GFR by BSA.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, if non-indexed GFR is considered, there is an expected difference of mGFR in men and women as body size is different according to gender. This point has been nicely illustrated in the RENIS cohort study [31] . Also, we and others have criticized the indexation of GFR by BSA.…”
Section: Discussionmentioning
confidence: 75%
“…Without the Peters data, the mean mGFR in the 30-40 years age group becomes 105.6 with a 95% CI of 103.4-107.8, which includes 107. The second key message of our meta-analysis is that mean mGFR is not different between men and women, at least not before the age of 50 years [9,31], and thus, there is no need to build in an extra multiplication factor for gender at the GFR level, when the correction for differences in Scr generation has already been done at the Scr level. At this point, we have to comment on the indexation by BSA.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that such overestimations of mGFR may result from exaggerated correction of the distribution volume of creatinine when indexing to extreme BSA levels. Instead it has been proposed that GFR should be indexed against total body water [42]. Measuring GFR instead of estimating GFR may still be preferable in very low and very high BMI.…”
Section: Results In Relation To Previous Studiesmentioning
confidence: 99%
“…However, a more sensible approach is to use an age-adjusted GFR for both the MDRD-and CKD-EPI-based prediction of bSCr. We used age-and gender-adjusted mean values of GFR as measured and published by Wesson in 1969, values that were also described in the KDIGO 2012 Guidelines (16,20): by analyzing the association between age and GFR for healthy women and men aged between 20 and 89 years, a piecewise linear function was developed to describe the association of GFR with age based on the urinary clearance of inulin (16) We also included estimated total body water (TBW) as an additional predictor variable (21). Both age and TBW were used as predictor variables separately for men and women, and linear and nonlinear models were fitted.…”
Section: Baseline Scr Estimationsmentioning
confidence: 99%